$Herschel$-ATLAS:The connection between star formation and AGN activity in radio-loud and radio-quiet active galaxies - Gurkan, G; Hardcastle, M; Jarvis, M; Smith, D; Bourne, N; Dunne, L; Maddox, S; Ivison, R; Fritz, J (Oxford University Press, 2015)
We examine the relationship between star formation and AGN activity by constructing matched samples of local radio-loud and radio-quiet AGN in the HerschelATLAS fields. Radio-loud AGN are classified as high-excitation and low-excitation radio galaxies (HERGs, LERGs) using their emission lines and WISE 22-μm luminosity. AGN accretion and jet powers in these active galaxies are traced by [OIII] emission-line and radio luminosity, respectively. Star formation rates (SFRs) and specific star formation rates (SSFRs) were derived using Herschel 250-μm luminosity and stellar mass measurements from the SDSS MPA-JHU catalogue. In the past, star formation studies of AGN have mostly focused on high-redshift sources to observe the thermal dust emission that peaks in the far-infrared, which limited the samples to powerful objects. However, with Herschel we can expand this to low redshifts. Our stacking analyses show that SFRs and SSFRs of both radio-loud and radioquiet AGN increase with increasing AGN power but that radio-loud AGN tend to have lower SFR. Additionally, radio-quiet AGN are found to have approximately an order of magnitude higher SSFRs than radio-loud AGN for a given level of AGN power. The difference between the star formation properties of radio-loud and -quiet AGN is also seen in samples matched in stellar mass.